FITRAH MANUSIA SEBAGAI MODAL KESALEHAN INDIVIDUAL - Hudi, Saman (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
Discourses on human nature based on Qur'anic verses and hadith have resulted in many differences of opinion in two major areas. First, regarding the interpretation of the hadith, which positions nature in opposition to non-Islamic religions, particularly Judaism, Christianity, and Zoroastrianism, rather than Islam. In this case, a child's conversion is determined by his or her parents. Second, the interpretation of the text of the Koran Surah Al A'raf verse 172 about taking testimony regarding the existence of God in the pre-existential human soul (while saying: "Am I not your God?" They responded, "Yes (You are our God), we are witnesses." Where humans lack rational awareness, prospective humans have acknowledged and believed that Allah is their god through their innate awareness. This innate awareness will become the capital of individual piety toward social piety. Keyword: Human Nature, individual piety